On the genus Tegestria Roewer, 1936, new senior synonym of Gintingius Roewer, 1938 with the description of a new species (Opiliones: Epedanidae: Sarasinicinae) - Zhang, Chao; Zhao, Jing Jing; Martens, Jochen (Zootaxa, 2023)
Tegestria altmannae sp. nov. is described and illustrated based on male and female specimens collected in Malaysia. It is characterized by the unarmed dorsal scutum, and basal segment of chelicerae dorsally with three seta-tipped tubercles. The type species of the monotypic genus Gintingius Roewer, 1938, G. robustus Roewer, 1938, is treated as a new synonym of Tegestria coniata Roewer, 1938 and the genus Gintingius as a new synonym of Tegestria Roewer, 1936, accordingly.